Establishment and development of intestinal microbiota in preterm neonates - Arboleya, Silvia (2012)
Microbial colonization of the infant gut is essential for the development of the intestine and the immune system. The profile of intestinal microbiota in the full-term, vaginally delivered, breast-fed infant is considered as ideally healthy. However, in preterm infants this process is challenging, mainly because of organ immaturity, antibiotics use, and hospital stay. To assist in a proper microbiota development in these infants, a detailed knowledge of the colonization process, and the differences from that of full-term breast-fed infants, is needed. We assessed the establishment of the gut microbiota and its metabolic activity in preterm neonates (n = 21) during the first 3 months of life and compared it with that of vaginally delivered, exclusively breast-fed full-term infants (n = 20) using qualitative and quantitative culture-independent methods. Differences in the gut microbiota composition between both groups were observed. Preterm infants showed higher levels of facultative anaerobic microorganisms and reduced levels of strict anaerobes such as Bifidobacterium, Bacteroides, and Atopobium. Short-chain fatty acids concentrations were lower in preterm infants during the first days of life. Alterations occur in the process of microbiota establishment in preterm infants, indicating the need for intervention strategies to counteract them.